(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
Core Ban 89-22 GC has been recovered in the Bannock Basin (Eastern Mediterranean) on the large sill separaring Borea and Maestro sub-basins in an area covered by high density brines. The interest of this core consists in its dolomitic composition, for this reason the core has been studied in its sedimentological and micropaleontological characters with great detail. The use of particular analyses (C.A.T. Computerized axial tomography, carbonate percentage, smear-slides observations of all samples for the identification of nannofossil Zones and for the mineralogic composition of the sediments, EDAX) allows to explain the dolomitic composition as secondary diagenization due to the upward molecular diffusion or advection of Mg++ ions from the dissolution of primary dolomite of Messinian age, recovered in the core-catcher thus in contact with the Pleistocene-Holocene core sediments.